Ultrahigh-voltage pulse strontium titanate annular piezoresistor and preparation method thereof
By introducing specific components and nanomaterials into the strontium titanate annular varistor, the pulse resistance, nonlinear coefficient and capacitance value of the resistor are improved, and the problem of insufficient performance of traditional resistors is solved and the development of high-performance resistors is realized.
Patent Information
- Application Number
- CN202411772692.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-18
AI Technical Summary
The traditional strontium titanate annular varistors above 48V have shortcomings in pulse resistance, nonlinear coefficient and capacitance value, and cannot meet market demand.
The formula of ultra-high voltage pulsed strontium titanate annular varistor is adopted, including strontium carbonate, barium carbonate, calcium carbonate, titanium dioxide, niobium oxide, silica, aluminum dioxide, manganese carbonate, tin dioxide and zinc oxide. The overall strength and pulse resistance of the resistance are improved through the combination of multi-layer nanofiber materials and three-dimensional composite nanomaterials.
It realizes a varistor with high pulse resistance, nonlinear coefficient and capacitance value, small loss and high flexural strength, which meets the market's demand for high-performance resistors.
Smart Images

Figure BDA0005170629810000141 
Figure BDA0005170629810000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of varistor preparation, and in particular to an ultra-high voltage pulse strontium titanate annular varistor and a preparation method thereof. Background Art
[0002] In recent years, my country's economy has continued to maintain rapid development, people's living standards are getting higher and higher, there are more and more high-end household appliances, and the quality requirements for household appliances are getting higher and higher. The high requirements for the quality of household appliances are actually high requirements for their components. Micromotors are a very important component in household appliances. They are the "power source" of household appliances. Now SrTiO is used in micromotors. 3 Varistors are already quite common, especially in mid-range and high-end audio equipment. 3 Varistors can be used to eliminate the noise generated by micromotor circuit systems, extend the service life of micromotors, etc.
[0003] Strontium titanate varistors are made of strontium titanate as the main raw material. After compression molding and debinding, the grains and green sheets are first made semiconductive through the combined action of donor doping and sintering in a reducing atmosphere. The grain boundaries and the outer layer of the green sheet are then made highly resistive and insulated through the combined action of acceptor doping and high-temperature oxidation, thereby obtaining a surface layer semiconductor substrate. Electrodes are then screen-printed and infiltrated, and finally a semiconductor ceramic sensitive device with dual functions of nonlinear varistor characteristics and capacitance characteristics is obtained.
[0004] Traditional strontium titanate annular varistors above 48V have a first main component mainly composed of Sr, Ba, Ca and Ti, a second component composed of at least one type of oxides of M (Nb and Ta), and a third component composed of oxides of Si. This formula requires repeated oxidation when making a varistor with an E10 value voltage greater than 48V, and has poor pulse resistance, which cannot meet the demand. Based on this, a varistor with strong pulse resistance, high nonlinear coefficient, high capacitance, low loss, and high flexural strength is urgently needed to meet market demand. Summary of the invention
[0005] In view of the problems mentioned in the above background technology, the purpose of the present invention is to provide an ultra-high voltage pulse strontium titanate ring varistor and a preparation method thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] An ultra-high voltage pulse strontium titanate annular varistor, comprising the following components in parts by weight: 20-25 parts of strontium carbonate, 20-25 parts of barium carbonate, 11-15 parts of calcium carbonate, 33-36 parts of titanium dioxide, 0.17-0.20 parts of niobium oxide, 0.1-0.3 parts of silicon dioxide, 0.01-0.20 parts of aluminum oxide, 0.01-0.50 parts of manganese carbonate, 5-10 parts of tin dioxide, 0.01-0.20 parts of zinc oxide, and 0.2-0.7 parts of nanomaterials;
[0008] The nano material is composed of multi-layer nano fiber material and three-dimensional composite nano material in a mass ratio of (7-10):1.
[0009] As a further preferred embodiment of the present invention, the preparation method of the multilayer nanofiber material is as follows:
[0010] 1) Fix the filter paper on the mobile phase filtration device, add 10-30mL of tetrabutyl titanate solution into the filter cup, slowly filter out half of the solution under suction filtration, while ensuring that the solution fully soaks the filter paper, let it stand for 5-10 minutes, then slowly filter out the remaining tetrabutyl titanate, and when the solution level approaches the surface of the filter paper, quickly add 10-30mL of anhydrous ethanol, and then slowly filter out half of it, repeat adding anhydrous ethanol and filtering 3-5 times, and continue to soak the remaining anhydrous ethanol for 5-10 minutes;
[0011] 2) After the soaking is completed, the remaining anhydrous ethanol is vacuum filtered, and then 20-50 mL of deionized water is added, and the filter paper is slowly filtered to half, and the filter paper is allowed to stand for 3-8 minutes. After the standing is completed, the remaining deionized water is vacuum filtered, and a large amount of anhydrous ethanol is used for filtering and washing to remove the residual water, and then the filter paper is filtered for 15-30 minutes to fully dry the filter paper, and the operation of steps 1)-2) is repeated 3-5 times to obtain the pretreated filter paper;
[0012] 3) Fixing the pre-treated filter paper on the mobile phase filtration device, adding 10-30 mL of tin hydroxide solution into the filter cup, slowly filtering out half of the solution, letting it stand for 5-10 minutes, then slowly filtering out the remaining tin hydroxide solution, adding 20-50 mL of deionized water and filtering it completely, then adding 20-50 mL of anhydrous ethanol, filtering it for 15-30 minutes, making the filter paper fully dry, repeating the operation of step 3) for 8-10 times, and obtaining a composite filter paper material;
[0013] 4) Repeat the above operation 3-4 times, then heat the obtained composite filter paper material from room temperature to 550-580° C. in an inert atmosphere and keep the temperature constant for 6-10 hours. After the treatment is completed, cool it naturally to room temperature to obtain a multilayer nanofiber material.
[0014] As a further preferred embodiment of the present invention, in step 1), the concentration of tetrabutyl titanate is 0.2-0.5 mol / L.
[0015] As a further preferred embodiment of the present invention, in step 2), the suction filtration and washing are performed 3-5 times.
[0016] As a further preferred embodiment of the present invention, in step 3), the concentration of the tin hydroxide solution is 0.2-0.5 mol / L.
[0017] As a further preferred embodiment of the present invention, in step 4), the heating rate is 5-8°C / min.
[0018] As a further preferred embodiment of the present invention, the preparation method of the three-dimensional composite nanomaterial is as follows:
[0019] 1) dissolving sodium dodecyl sulfate in a mixed solution consisting of deionized water and n-butanol in a volume ratio of (3.0-3.5):1, stirring thoroughly until completely dissolved, to obtain a sodium dodecyl sulfate solution; separately weighing zinc acetate dihydrate and urea, dissolving them in deionized water, stirring thoroughly to dissolve, and then slowly dropping them into the sodium dodecyl sulfate solution, stirring rapidly until clarified, to obtain a mixed solution;
[0020] 2) Add multi-walled carbon nanotubes to the mixed solution at a solid-liquid ratio of 1 g: (30-50) mL, and after ultrasonic dispersion, transfer to a high-pressure reactor, keep warm at 100-110° C. for 12-15 hours, cool to room temperature after the reaction is completed, wash repeatedly with deionized water and anhydrous ethanol, and then dry, and then put into a high-temperature resistance furnace, calcine for 2-3 hours in an air atmosphere, and obtain a three-dimensional composite nanomaterial after natural cooling.
[0021] As a further preferred embodiment of the present invention, in step 1), the dosage ratio of the sodium dodecyl sulfate, the mixed solution, zinc acetate dihydrate, urea and deionized water is (0.25-0.40) g: (40-50) mL: (5-8) mmol: (40-75) mmol: (50-90) mL.
[0022] As a further preferred embodiment of the present invention, in step 2), the calcination temperature is 450-470°C.
[0023] A method for preparing an ultra-high voltage pulse strontium titanate ring varistor specifically comprises the following steps:
[0024] a. Stirring and grinding: Mix the components according to weight to obtain powder, then weigh according to the required ratio, mix the powder: water: dispersant according to the mass ratio of 1: (0.5-0.8): (0.012-0.015), add water first, then dispersant, and finally powder, the speed is 2100-2700r / min, and grind for 4-6h. Among them, polyethylene glycol is used as the dispersant;
[0025] b. Spray granulation: The inlet temperature of the granulator is 240-280℃, the outlet temperature is 80-120℃, and the atomizer speed is 6700-7300r / min, so that the particle size is controlled at 70-100um and the moisture content of the powder is less than 0.4%;
[0026] c. Powder sintering synthesis: Fully synthesize at 1180-1220℃, with the powder loss rate reaching more than 18%;
[0027] d. Secondary stirring and grinding: weigh according to the required ratio, mix the powder: water: dispersant: release agent in the mass ratio of 1: (0.5-0.8): (0.015-0.018): (0.030-0.035), add water first, then dispersant, and finally powder, grind for 8-10 hours, add release agent, and continue grinding for 1-3 hours. The dispersant is polyethylene glycol and the release agent is polyethylene wax;
[0028] e. Secondary spray granulation: the inlet temperature of the granulator is 240-280℃, the outlet temperature is 80-120℃, and the speed of the atomizer is 6700-7300r / min; the ground slurry is granulated so that the particle size is controlled at 70-100um and the moisture content of the powder is less than 0.4%;
[0029] f. Dry pressing: The powder is dry pressed by a dry pressing machine. The density of the green embryo is 3.2-3.4g / cm 3 ;
[0030] g. Debinding sintering: Debinding the green sheet at 1100-1200℃ to remove glue, impurities and organic matter, and harden the green sheet to form a debinding sheet;
[0031] h. Reduction sintering: sinter the debonding sheet at 1380-1420°C in a mixed atmosphere of nitrogen and hydrogen in a volume ratio of 1:3 to form a reduction sheet;
[0032] i. Oxidation sintering: sinter the reduction sheet at 800-1000°C in air to form an oxide sheet;
[0033] j. Silver printing: First print a layer of ohmic paste on the oxide sheet, dry it at 180-183℃, print a layer of silver on the ohmic layer, and dry it;
[0034] k. Silver sintering: Sinter the printed and dried product in air at 580-620℃. Use a ring varistor sorter to sort out the qualified voltage of the sintered silver sheet to obtain the required ultra-high voltage pulse strontium titanate ring varistor.
[0035] The beneficial effects of the present invention are:
[0036] In the present invention, laboratory filter paper is used as a support, tin hydroxide is used as a precursor of tin dioxide, and tetrabutyl titanate is used as a precursor of titanium dioxide. After the prepared tetrabutyl titanate solution is soaked in the filter paper, it is first adsorbed on the surface of the filter paper through hydrogen bonds. After deionized water is added, tetrabutyl titanate and hydroxyl groups on the surface of the filter paper are dealcoholized and condensed to react on the surface of the cellulose material to form a layer of titanium dioxide gel, the surface of which contains a large number of hydroxyl groups. After the tin hydroxide solution is added, the tin hydroxide is dehydrated and condensed with the hydroxyl groups regenerated on the surface of the titanium dioxide gel layer, and this process is repeated to form a multilayer TiO 2 / SnO 2 The composite of gel layer and filter paper fiber is calcined in an inert atmosphere, and the cellulose in the composite is converted into a C skeleton as an organic component, and SnO 2 and TiO 2 The crystallized nanoparticles are sequentially stacked and distributed on the C skeleton. By adjusting the assembly order of tin dioxide and titanium dioxide, the assembly of different alternating layers between tin dioxide and titanium dioxide is achieved, thereby obtaining a multilayer nanofiber material. The multilayer nanofiber material presents a carbon fiber as the matrix, and a multilayer alternating structure of TiO2 is deposited on the surface. 2 / SnO 2The deposited multilayer nanoparticles can, on the one hand, fill the defects on the surface of the carbon fiber and enhance the overall strength of the carbon fiber. At the same time, they can also effectively increase the roughness and specific surface area of the carbon fiber surface and expand the contact area between the carbon fibers. At the same time, zinc acetate dihydrate is used as the zinc source and multi-walled carbon nanotubes are used as the deposition matrix. A large number of nanoparticles with flower-like three-dimensional structures are deposited on the multi-walled carbon nanotubes by a hydrothermal method, thereby obtaining a three-dimensional composite nanomaterial. By adding it to the powder together with the multilayer nanofiber material, in the process of sufficient stirring and grinding, since the multilayer nanofiber material has a large number of multilayer nanoparticles on its surface, after being embedded in the pores of the material components, it can form a strong friction with the material particles, thereby stably existing in the material, while achieving the improvement of the material density, it also It can play the role of limiting the solid material particles, which is beneficial to the subsequent dry pressing process, so that the material can be compacted tightly; at the same time, since the surface of the three-dimensional composite nanomaterial has a large number of flower-like three-dimensional structures, the protruding flower-like lamellar structure can be embedded in the gaps between the multi-layer nanoparticles on the surface of the multi-layer nanofiber material, and the multi-walled carbon nanotube structure can be entangled with the multi-layer nanofiber material, so that inside the material, the multi-layer nanofiber material is connected to form an integrated network-like three-dimensional structure, which can not only better limit the solid material particles and improve the density of the material, but also the formed network-like three-dimensional structure plays the role of a supporting skeleton in the material, strengthening the overall strength of the material, so that the annular varistor after molding has a dense structure, high strength, strong resistance to external forces, and good flexural strength.
[0037] In a conventional varistor, a first main component is mainly composed of Sr, Ba, Ca and Ti, a second component is composed of at least one type of oxide of M (Nb and Ta), and a third component is composed of oxide of Si. In the present invention, aluminum oxide, manganese carbonate, tin dioxide and zinc oxide are added to the conventional formula to achieve the purpose of improving pulse resistance, improving nonlinear coefficient and capacitance value, and reducing loss. At the same time, the introduced multi-layer nanofiber material and three-dimensional composite nanomaterial can effectively enhance the overall strength of the material through mutual cooperation, so that the annular varistor after molding has a dense structure, high strength, strong resistance to external force, and good flexural strength, thereby achieving the effect of increasing the strength of the porcelain body. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Example 1
[0040] An ultra-high voltage pulse strontium titanate annular varistor, comprising the following components in parts by weight: 20 parts of strontium carbonate, 20 parts of barium carbonate, 11 parts of calcium carbonate, 33 parts of titanium dioxide, 0.17 parts of niobium oxide, 0.1 parts of silicon dioxide, 0.01 parts of aluminum oxide, 0.01 parts of manganese carbonate, 5 parts of tin dioxide, 0.01 parts of zinc oxide, and 0.2 parts of nanomaterials;
[0041] Among them, the nanomaterial is composed of multi-layer nanofiber material and three-dimensional composite nanomaterial in a mass ratio of 7:1;
[0042] The preparation method of the ultra-high voltage pulse strontium titanate ring varistor specifically comprises the following steps:
[0043] a. Stirring and grinding: Mix the components according to weight to obtain powder, then weigh according to the required ratio, mix the powder: water: dispersant at a mass ratio of 1:0.5:0.012, add water first, then dispersant, and finally powder, rotate at 2100r / min, grind for 4h, wherein polyethylene glycol is selected as the dispersant;
[0044] b. Spray granulation: The inlet temperature of the granulator is 240℃, the outlet temperature is 80℃, and the atomizer speed is 6700r / min, so that the particle size is controlled at 70um and the moisture content of the powder is less than 0.4%;
[0045] c. Powder sintering synthesis: Full synthesis reaction is carried out at a temperature of 1180℃, and the powder loss rate is more than 18%;
[0046] d. Secondary stirring and grinding: weigh according to the required ratio, mix the powder: water: dispersant: release agent in the mass ratio of 1:0.5:0.015:0.030, add water first, then dispersant, and finally powder, grind for 8 hours, add release agent, and continue grinding for 1 hour. The dispersant is polyethylene glycol and the release agent is polyethylene wax;
[0047] e. Secondary spray granulation: the inlet temperature of the granulator is 240℃, the outlet temperature is 80℃, and the speed of the atomizer is 6700r / min; the ground slurry is granulated so that the particle size is controlled at 70um and the moisture content of the powder is less than 0.4%;
[0048] f. Dry pressing: The powder is dry pressed by a dry pressing machine. The density of the green embryo is 3.2g / cm 3 ;
[0049] g. Debinding sintering: Debinding the green sheet at 1100°C to remove glue, impurities and organic matter, and harden the green sheet to form a debinding sheet;
[0050] h. Reduction sintering: sinter the debonding sheet at 1380°C in a mixed atmosphere of nitrogen and hydrogen with a volume ratio of 1:3 to form a reduction sheet;
[0051] i. Oxidation sintering: sinter the reduction sheet at 800°C in air to form an oxide sheet;
[0052] j. Silver printing: First print a layer of ohmic paste on the oxide sheet, dry it at 180°C, print a layer of silver on the ohmic layer, and dry it;
[0053] k. Silver sintering: Sinter the printed and dried product at 580°C in air, and use a ring varistor sorter to sort out the qualified voltage from the sintered silver sheets to obtain the required ultra-high voltage pulse strontium titanate ring varistor.
[0054] The preparation method of the multilayer nanofiber material is as follows:
[0055] 1) Fix the filter paper on the mobile phase filtration device, add 10mL of 0.2mol / L tetrabutyl titanate solution into the filter cup, slowly filter out half of the solution under suction filtration, while ensuring that the solution fully soaks the filter paper, let it stand for 5 minutes, then slowly filter out the remaining tetrabutyl titanate, and when the solution level approaches the surface of the filter paper, quickly add 10mL of anhydrous ethanol, then slowly filter out half of it, repeat adding anhydrous ethanol and filtering 3 times, and continue to soak the remaining anhydrous ethanol for 5 minutes;
[0056] 2) After the soaking is completed, the remaining anhydrous ethanol is vacuum filtered, and then 20 mL of deionized water is added, and the mixture is slowly filtered to half, and the mixture is allowed to stand for 3 minutes. After the standing is completed, the remaining deionized water is vacuum filtered, and a large amount of anhydrous ethanol is used for filtration and washing 3 times to remove the residual water, and then the filter paper is filtered for 15 minutes to fully dry the filter paper, and the operation of steps 1)-2) is repeated 3 times to obtain the pretreated filter paper;
[0057] 3) Fix the pre-treated filter paper on the mobile phase filtration device, add 10 mL of 0.2 mol / L tin hydroxide solution into the filter cup, slowly filter out half of the solution, let it stand for 5 minutes, then slowly filter out the remaining tin hydroxide solution, add 20 mL of deionized water and filter it completely, then add 20 mL of anhydrous ethanol and filter it for 15 minutes to fully dry the filter paper, repeat the operation of step 3) 8 times to obtain a composite filter paper material;
[0058] 4) Repeat the above operation three times, then heat the obtained composite filter paper material from room temperature to 550°C at a rate of 5°C / min under an inert atmosphere and keep the constant temperature for 6 hours. After the treatment, cool it naturally to room temperature to obtain a multilayer nanofiber material.
[0059] Wherein, the preparation method of three-dimensional composite nanomaterial is as follows:
[0060] 1) Dissolve 0.25 g of sodium dodecyl sulfate in 40 mL of a mixture of deionized water and n-butanol in a volume ratio of 3:1, and stir thoroughly until completely dissolved to obtain a sodium dodecyl sulfate solution. Separately weigh 5 mmol of zinc acetate dihydrate and 40 mmol of urea, dissolve them in 50 mL of deionized water, stir thoroughly to dissolve, and then slowly dropwise add them to the sodium dodecyl sulfate solution, and stir rapidly until clear to obtain a mixed solution.
[0061] 2) Add multi-walled carbon nanotubes to the mixed solution at a solid-liquid ratio of 1 g:30 mL, and after ultrasonic dispersion, transfer to a high-pressure reactor and keep warm at 100°C for 12 h. After the reaction is completed, cool to room temperature, wash repeatedly with deionized water and anhydrous ethanol, and then dry. Then, place in a high-temperature resistance furnace and calcine at 450°C in an air atmosphere for 2 h. After natural cooling, a three-dimensional composite nanomaterial is obtained.
[0062] Example 2
[0063] An ultra-high voltage pulse strontium titanate annular varistor, comprising the following components in parts by weight: 23 parts of strontium carbonate, 23 parts of barium carbonate, 13 parts of calcium carbonate, 35 parts of titanium dioxide, 0.18 parts of niobium oxide, 0.2 parts of silicon dioxide, 0.15 parts of aluminum oxide, 0.32 parts of manganese carbonate, 7 parts of tin dioxide, 0.15 parts of zinc oxide, and 0.5 parts of nanomaterials;
[0064] Among them, the nanomaterial is composed of multi-layer nanofiber material and three-dimensional composite nanomaterial in a mass ratio of 8:1;
[0065] The preparation method of the ultra-high voltage pulse strontium titanate ring varistor specifically comprises the following steps:
[0066] a. Stirring and grinding: Mix the components according to weight to obtain powder, then weigh according to the required ratio, mix the powder: water: dispersant at a mass ratio of 1:0.7:0.013, add water first, then dispersant, and finally powder, rotate at 2400r / min, grind for 5h, wherein polyethylene glycol is selected as the dispersant;
[0067] b. Spray granulation: The inlet temperature of the granulator is 260℃, the outlet temperature is 100℃, and the atomizer speed is 7000r / min, so that the particle size is controlled at 80um and the moisture content of the powder is less than 0.4%;
[0068] c. Powder sintering synthesis: Full synthesis reaction is carried out at a temperature of 1200℃, and the powder loss rate is more than 18%;
[0069] d. Secondary stirring and grinding: weigh according to the required ratio, mix the powder: water: dispersant: release agent in the mass ratio of 1: 0.7: 0.017: 0.032, add water first, then dispersant, and finally powder, grind for 9 hours, add release agent, and continue grinding for 2 hours. The dispersant is polyethylene glycol and the release agent is polyethylene wax;
[0070] e. Secondary spray granulation: the inlet temperature of the granulator is 260℃, the outlet temperature is 100℃, and the speed of the atomizer is 7000r / min; the ground slurry is granulated so that the particle size is controlled at 80um and the moisture content of the powder is less than 0.4%;
[0071] f. Dry pressing: The powder is dry pressed by a dry pressing machine. The density of the green embryo is 3.3g / cm 3 ;
[0072] g. Debinding sintering: Debinding the green sheet at 1150°C to remove glue, impurities and organic matter, and harden the green sheet to form a debinding sheet;
[0073] h. Reduction sintering: sinter the debonding sheet at 1400°C in a mixed atmosphere of nitrogen and hydrogen with a volume ratio of 1:3 to form a reduction sheet;
[0074] i. Oxidation sintering: sinter the reduction sheet at 900°C in air to form an oxide sheet;
[0075] j. Silver printing: First print a layer of ohmic paste on the oxide sheet, dry it at 182°C, print a layer of silver on the ohmic layer, and dry it;
[0076] k. Silver sintering: Sinter the printed and dried product in air at 600°C. Use a ring varistor sorter to sort out the sintered silver sheets with qualified voltage to obtain the required ultra-high voltage pulse strontium titanate ring varistor.
[0077] The preparation method of the multilayer nanofiber material is as follows:
[0078] 1) Fix the filter paper on the mobile phase filtration device, add 20 mL of 0.3 mol / L tetrabutyl titanate solution into the filter cup, slowly filter out half of the solution under suction filtration, while ensuring that the solution fully soaks the filter paper, let it stand for 7 minutes, and then slowly filter out the remaining tetrabutyl titanate. When the solution level approaches the surface of the filter paper, quickly add 20 mL of anhydrous ethanol, and then slowly filter out half of it, repeat adding anhydrous ethanol and filtering 4 times, and continue to soak the remaining anhydrous ethanol for 7 minutes;
[0079] 2) After the soaking is completed, the remaining anhydrous ethanol is vacuum filtered, and then 35 mL of deionized water is added, and the mixture is slowly filtered to half, and the mixture is allowed to stand for 5 minutes. After the standing is completed, the remaining deionized water is vacuum filtered, and a large amount of anhydrous ethanol is used for filtration and washing 4 times to remove the residual water, and then the filter paper is filtered for 25 minutes to fully dry the filter paper, and the operation of steps 1)-2) is repeated 4 times to obtain the pretreated filter paper;
[0080] 3) Fix the pre-treated filter paper on the mobile phase filtration device, add 20 mL of 0.3 mol / L tin hydroxide solution into the filter cup, slowly filter out half of the solution, let it stand for 7 minutes, then slowly filter out the remaining tin hydroxide solution, add 35 mL of deionized water and filter it completely, then add 35 mL of anhydrous ethanol and filter it for 25 minutes to fully dry the filter paper, repeat the operation of step 3) for 9 times to obtain a composite filter paper material;
[0081] 4) Repeat the above operation three times, then heat the obtained composite filter paper material from room temperature to 560°C at a rate of 6°C / min under an inert atmosphere and keep the constant temperature for 8 hours. After the treatment is completed, cool it naturally to room temperature to obtain a multilayer nanofiber material.
[0082] Wherein, the preparation method of three-dimensional composite nanomaterial is as follows:
[0083] 1) Dissolve 0.32 g of sodium dodecyl sulfate in 45 mL of a mixture of deionized water and n-butanol in a volume ratio of 3.2:1, and stir thoroughly until completely dissolved to obtain a sodium dodecyl sulfate solution. Separately weigh 7 mmol of zinc acetate dihydrate and 62 mmol of urea, dissolve them in 80 mL of deionized water, stir thoroughly to dissolve, and then slowly dropwise add them to the sodium dodecyl sulfate solution, and stir rapidly until clear to obtain a mixed solution.
[0084] 2) Add multi-walled carbon nanotubes to the mixed solution at a solid-liquid ratio of 1 g:40 mL, and after ultrasonic dispersion, transfer to a high-pressure reactor and keep warm at 105°C for 13 h. After the reaction is completed, cool to room temperature, wash repeatedly with deionized water and anhydrous ethanol, and then dry. Then, place in a high-temperature resistance furnace and calcine at 460°C in an air atmosphere for 2.5 h. After natural cooling, a three-dimensional composite nanomaterial is obtained.
[0085] Example 3
[0086] An ultra-high voltage pulse strontium titanate annular varistor, comprising the following components in parts by weight: 25 parts of strontium carbonate, 25 parts of barium carbonate, 15 parts of calcium carbonate, 36 parts of titanium dioxide, 0.20 parts of niobium oxide, 0.3 parts of silicon dioxide, 0.20 parts of aluminum oxide, 0.50 parts of manganese carbonate, 10 parts of tin dioxide, 0.20 parts of zinc oxide, and 0.7 parts of nanomaterials;
[0087] Among them, the nanomaterial is composed of multi-layer nanofiber material and three-dimensional composite nanomaterial in a mass ratio of 10:1;
[0088] The preparation method of the ultra-high voltage pulse strontium titanate ring varistor specifically comprises the following steps:
[0089] a. Stirring and grinding: Mix the components according to weight to obtain powder, then weigh according to the required ratio, mix the powder: water: dispersant at a mass ratio of 1:0.8:0.015, add water first, then dispersant, and finally powder, rotate at 2700r / min, grind for 6h, wherein polyethylene glycol is selected as the dispersant;
[0090] b. Spray granulation: The inlet temperature of the granulator is 280℃, the outlet temperature is 120℃, and the atomizer speed is 7300r / min, so that the particle size is controlled at 100um and the moisture content of the powder is less than 0.4%;
[0091] c. Powder sintering synthesis: Full synthesis reaction is carried out at a temperature of 1220℃, and the powder loss rate is more than 18%;
[0092] d. Secondary stirring and grinding: weigh according to the required ratio, mix the powder: water: dispersant: release agent in the mass ratio of 1:0.8:0.018:0.035, add water first, then dispersant, and finally powder, grind for 10 hours, add release agent, and continue grinding for 3 hours. The dispersant is polyethylene glycol and the release agent is polyethylene wax;
[0093] e. Secondary spray granulation: the inlet temperature of the granulator is 280℃, the outlet temperature is 120℃, and the speed of the atomizer is 7300r / min; the ground slurry is granulated so that the particle size is controlled at 100um and the moisture content of the powder is less than 0.4%;
[0094] f. Dry pressing: The powder is dry pressed by a dry pressing machine. The density of the green embryo is 3.4g / cm 3 ;
[0095] g. Debinding sintering: Debinding the green sheet at 1200°C to remove glue, impurities and organic matter, and harden the green sheet to form a debinding sheet;
[0096] h. Reduction sintering: sinter the debonding sheet at 1420°C in a mixed atmosphere of nitrogen and hydrogen with a volume ratio of 1:3 to form a reduction sheet;
[0097] i. Oxidation sintering: sinter the reduction sheet at 1000°C in air to form an oxide sheet;
[0098] j. Silver printing: First print a layer of ohmic paste on the oxide sheet, dry it at 183°C, print a layer of silver on the ohmic layer, and dry it;
[0099] k. Silver sintering: Sinter the printed and dried product at 620℃ in air. Use a ring varistor sorter to sort out the qualified voltage of the sintered silver sheets to obtain the required ultra-high voltage pulse strontium titanate ring varistor.
[0100] The preparation method of the multilayer nanofiber material is as follows:
[0101] 1) Fix the filter paper on the mobile phase filtration device, add 30mL of 0.5mol / L tetrabutyl titanate solution into the filter cup, slowly filter out half of the solution under suction filtration, while ensuring that the solution fully soaks the filter paper, let it stand for 10 minutes, then slowly filter out the remaining tetrabutyl titanate, and when the solution level approaches the surface of the filter paper, quickly add 30mL of anhydrous ethanol, and then slowly filter out half of it, repeat adding anhydrous ethanol and filtering 5 times, and continue to soak the remaining anhydrous ethanol for 10 minutes;
[0102] 2) After the soaking is completed, the remaining anhydrous ethanol is vacuum filtered, and then 50 mL of deionized water is added, and the mixture is slowly filtered to half, and the mixture is allowed to stand for 8 minutes. After the standing is completed, the remaining deionized water is vacuum filtered, and a large amount of anhydrous ethanol is used for suction and washing 5 times to remove the residual water, and then the filter paper is filtered for 30 minutes to fully dry the filter paper, and the operation of steps 1)-2) is repeated 5 times to obtain the pretreated filter paper;
[0103] 3) Fix the pre-treated filter paper on the mobile phase filtration device, add 30 mL of 0.5 mol / L tin hydroxide solution into the filter cup, slowly filter out half of the solution, let it stand for 10 minutes, then slowly filter out the remaining tin hydroxide solution, add 50 mL of deionized water and filter it completely, then add 50 mL of anhydrous ethanol and filter it for 30 minutes to fully dry the filter paper, repeat the operation of step 3) 10 times to obtain a composite filter paper material;
[0104] 4) Repeat the above operation 4 times, then heat the obtained composite filter paper material from room temperature to 580°C at a rate of 8°C / min under an inert atmosphere, and keep the constant temperature for 10 hours. After the treatment is completed, cool it naturally to room temperature to obtain a multilayer nanofiber material.
[0105] Wherein, the preparation method of three-dimensional composite nanomaterial is as follows:
[0106] 1) Dissolve 0.40 g of sodium dodecyl sulfate in 50 mL of a mixture of deionized water and n-butanol in a volume ratio of 3.5:1, and stir thoroughly until completely dissolved to obtain a sodium dodecyl sulfate solution. Separately weigh 8 mmol of zinc acetate dihydrate and 75 mmol of urea, dissolve them in 90 mL of deionized water, stir thoroughly to dissolve, and then slowly dropwise add them to the sodium dodecyl sulfate solution, and stir rapidly until clear to obtain a mixed solution.
[0107] 2) Add multi-walled carbon nanotubes to the mixed solution at a solid-liquid ratio of 1 g:50 mL, and after ultrasonic dispersion, transfer to a high-pressure reactor and keep warm at 110°C for 15 h. After the reaction is completed, cool to room temperature, wash repeatedly with deionized water and anhydrous ethanol, and then dry. Then, place in a high-temperature resistance furnace and calcine at 470°C in an air atmosphere for 3 h. After natural cooling, a three-dimensional composite nanomaterial is obtained.
[0108] Comparative Example 1: This comparative example is substantially the same as Example 1, except that it does not contain multiple layers of nanofiber material.
[0109] Comparative Example 2: This comparative example is basically the same as Example 1, except that it does not contain three-dimensional composite nanomaterials.
[0110] Comparative Example 3: This comparative example is basically the same as Example 1, except that in the preparation of the multilayer nanofiber material, steps 1)-2) are omitted.
[0111] Comparative Example 4: This comparative example is basically the same as Example 1, except that step 3) is omitted in the preparation of the multilayer nanofiber material.
[0112] Comparative Example 5: This comparative example is basically the same as Example 1, except that multi-walled carbon nanotubes are used instead of three-dimensional composite nanomaterials.
[0113] Control group: This control group is basically the same as Example 1, except that it does not contain multilayer nanofiber material and three-dimensional composite nanomaterial.
[0114] Test experiment:
[0115] According to the methods of Examples 1-3, Comparative Examples 1-5 and the control group, strontium titanate annular varistor samples were processed respectively, and then the flexural strength of each sample was tested using a universal universal material testing machine. The data obtained in the control group was used as a reference to record the data obtained in Examples 1-3 and Comparative Examples 1-5, and the changes relative to the control group are shown in Table 1.
[0116] Table 1
[0117]
[0118]
[0119] It can be seen from Table 1 that the strontium titanate annular varistor in the present invention has strong resistance to external forces and good flexural strength, thereby achieving the effect of increasing the strength of the porcelain body.
[0120] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. An ultra-high voltage pulse strontium titanate ring varistor, characterized in that: The ultra-high voltage pulse strontium titanate annular varistor comprises the following components in parts by weight: 20-25 parts of strontium carbonate, 20-25 parts of barium carbonate, 11-15 parts of calcium carbonate, 33-36 parts of titanium dioxide, 0.17-0.20 parts of niobium oxide, 0.1-0.3 parts of silicon dioxide, 0.01-0.20 parts of aluminum oxide, 0.01-0.50 parts of manganese carbonate, 5-10 parts of tin dioxide, 0.01-0.20 parts of zinc oxide, and 0.2-0.7 parts of nanomaterials; The nano material is composed of multi-layer nano fiber material and three-dimensional composite nano material in a mass ratio of (7-10):
1.
2. The ultra-high voltage pulse strontium titanate annular varistor according to claim 1, characterized in that: The preparation method of the multilayer nanofiber material is as follows: 1) Fix the filter paper on the mobile phase filtration device, add 10-30mL of tetrabutyl titanate solution into the filter cup, slowly filter out half of the solution under suction filtration, while ensuring that the solution fully soaks the filter paper, let it stand for 5-10 minutes, then slowly filter out the remaining tetrabutyl titanate, and when the solution level approaches the surface of the filter paper, quickly add 10-30mL of anhydrous ethanol, and then slowly filter out half of it, repeat adding anhydrous ethanol and filtering 3-5 times, and continue to soak the remaining anhydrous ethanol for 5-10 minutes; 2) After the soaking is completed, the remaining anhydrous ethanol is vacuum filtered, and then 20-50 mL of deionized water is added, and the filter paper is slowly filtered to half, and the filter paper is allowed to stand for 3-8 minutes. After the standing is completed, the remaining deionized water is vacuum filtered, and a large amount of anhydrous ethanol is used for filtering and washing to remove the residual water, and then the filter paper is filtered for 15-30 minutes to fully dry the filter paper, and the operation of steps 1)-2) is repeated 3-5 times to obtain the pretreated filter paper; 3) Fixing the pre-treated filter paper on the mobile phase filtration device, adding 10-30 mL of tin hydroxide solution into the filter cup, slowly filtering out half of the solution, letting it stand for 5-10 minutes, then slowly filtering out the remaining tin hydroxide solution, adding 20-50 mL of deionized water and filtering it completely, then adding 20-50 mL of anhydrous ethanol, filtering it for 15-30 minutes, making the filter paper fully dry, repeating the operation of step 3) for 8-10 times, and obtaining a composite filter paper material; 4) Repeat the above operation 3-4 times, then heat the obtained composite filter paper material from room temperature to 550-580° C. in an inert atmosphere and keep the temperature constant for 6-10 hours. After the treatment is completed, cool it naturally to room temperature to obtain a multilayer nanofiber material.
3. The ultra-high voltage pulse strontium titanate ring varistor according to claim 2, characterized in that: In step 1), the concentration of tetrabutyl titanate is 0.2-0.5 mol / L.
4. The ultra-high voltage pulse strontium titanate annular varistor according to claim 2, characterized in that: In step 2), the suction filtration and washing are performed 3-5 times.
5. The ultra-high voltage pulse strontium titanate ring varistor according to claim 2, characterized in that: In step 3), the concentration of the tin hydroxide solution is 0.2-0.5 mol / L.
6. The ultra-high voltage pulse strontium titanate annular varistor according to claim 2, characterized in that: In step 4), the heating rate is 5-8°C / min.
7. The ultra-high voltage pulse strontium titanate annular varistor according to claim 1, characterized in that: The preparation method of the three-dimensional composite nanomaterial is as follows: 1) dissolving sodium dodecyl sulfate in a mixed solution consisting of deionized water and n-butanol in a volume ratio of (3.0-3.5):1, stirring thoroughly until completely dissolved, to obtain a sodium dodecyl sulfate solution; separately weighing zinc acetate dihydrate and urea, dissolving them in deionized water, stirring thoroughly to dissolve, and then slowly dropping them into the sodium dodecyl sulfate solution, stirring rapidly until clarified, to obtain a mixed solution; 2) Add multi-walled carbon nanotubes to the mixed solution at a solid-liquid ratio of 1 g: (30-50) mL, and after ultrasonic dispersion, transfer to a high-pressure reactor, keep warm at 100-110° C. for 12-15 hours, cool to room temperature after the reaction is completed, wash repeatedly with deionized water and anhydrous ethanol, and then dry, and then put into a high-temperature resistance furnace, calcine for 2-3 hours in an air atmosphere, and obtain a three-dimensional composite nanomaterial after natural cooling.
8. The ultra-high voltage pulse strontium titanate annular varistor according to claim 7, characterized in that: In step 1), the dosage ratio of the sodium dodecyl sulfate, the mixed solution, zinc acetate dihydrate, urea, and deionized water is (0.25-0.40) g: (40-50) mL: (5-8) mmol: (40-75) mmol: (50-90) mL.
9. The ultra-high voltage pulse strontium titanate ring varistor according to claim 7, characterized in that: In step 2), the calcination temperature is 450-470°C.
10. A method for preparing an ultra-high voltage pulse strontium titanate ring varistor according to any one of claims 1 to 9, characterized in that: The specific steps include: a. Stirring and grinding: Mix the components according to weight to obtain powder, then weigh according to the required ratio, mix the powder: water: dispersant according to the mass ratio of 1: (0.5-0.8): (0.012-0.015), add water first, then dispersant, and finally powder, the speed is 2100-2700r / min, and grind for 4-6h. Among them, polyethylene glycol is used as the dispersant; b. Spray granulation: The inlet temperature of the granulator is 240-280℃, the outlet temperature is 80-120℃, and the atomizer speed is 6700-7300r / min, so that the particle size is controlled at 70-100um and the moisture content of the powder is less than 0.4%; c. Powder sintering synthesis: Fully synthesize at 1180-1220℃, with the powder loss rate reaching more than 18%; d. Secondary stirring and grinding: weigh according to the required ratio, mix the powder: water: dispersant: release agent in the mass ratio of 1: (0.5-0.8): (0.015-0.018): (0.030-0.035), add water first, then dispersant, and finally powder, grind for 8-10 hours, add release agent, and continue grinding for 1-3 hours. The dispersant is polyethylene glycol and the release agent is polyethylene wax; e. Secondary spray granulation: the inlet temperature of the granulator is 240-280℃, the outlet temperature is 80-120℃, and the speed of the atomizer is 6700-7300r / min; the ground slurry is granulated so that the particle size is controlled at 70-100um and the moisture content of the powder is less than 0.4%; f. Dry pressing: The powder is dry pressed by a dry pressing machine. The density of the green embryo is 3.2-3.4g / cm 3 ; g. Debinding sintering: Debinding the green sheet at 1100-1200℃ to remove glue, impurities and organic matter, and harden the green sheet to form a debinding sheet; h. Reduction sintering: sinter the debonding sheet at 1380-1420°C in a mixed atmosphere of nitrogen and hydrogen in a volume ratio of 1:3 to form a reduction sheet; i. Oxidation sintering: sinter the reduction sheet at 800-1000°C in air to form an oxide sheet; j. Silver printing: First print a layer of ohmic paste on the oxide sheet, dry it at 180-183℃, print a layer of silver on the ohmic layer, and dry it; k. Silver sintering: Sinter the printed and dried product in air at 580-620℃. Use a ring varistor sorter to sort out the qualified voltage of the sintered silver sheet to obtain the required ultra-high voltage pulse strontium titanate ring varistor.